John Whiteoak, ‘Take Me to Spain’: Australian Imaginings of Spain through Music and Dance. - Machin-Autenrieth, Matthew (Popular Music History, 2022)
John Whiteoak, ‘Take Me to Spain’: Australian Imaginings of Spain through Music and Dance. Melbourne: Lyrebird Press, 2019. 258 pp. ISBN 978-0-7340-3792-3 (pbk).